Nanocytological Field Carcinogenesis Detection to Mitigate Overdiagnosis of Prostate Cancer: A Proof of Concept Study - Roy, Hemant K.; Brendler, Charles B.; Subramanian, Hariharan; Zhang, Di; Maneval, Charles; Chandler, John; Bowen, Leah; Kaul, Karen L.; Helfand, Brian T.; Wang, Chi-Hsiung; Quinn, Margo; Petkewicz, Jacqueline; et al. (PloS one, 2015)
To determine whether nano-architectural interrogation of prostate field carcinogenesis can be used to predict prognosis in patients with early stage (Gleason 6) prostate cancer (PCa), which is mostly indolent but frequently unnecessarily treated. We previously developed partial wave spectroscopic microscopy (PWS) that enables quantification of the nanoscale intracellular architecture (20-200 nm length scale) with remarkable accuracy. We adapted this technique to assess prostate needle core biopsies in a case control study from men with Gleason 6 disease who either progressed (n = 20) or remained indolent (n = 18) over a ~3 year follow up. We measured the parameter disorder strength (Ld) characterizing the spatial heterogeneity of the nanoscale cellular structure and nuclear morphology from the microscopically normal mucosa ~150 histologically normal epithelial cells. There was a profound increase in nano-architectural disorder between progressors and non-progressors. Indeed, the Ld from future progressors was dramatically increased when compared to future non-progressors (1±0.065 versus 1.30±0.0614, respectively p = 0.002). The area under the receiver operator characteristic curve (AUC) was 0.79, yielding a sensitivity of 88% and specificity of 72% for discriminating between progressors and non-progressors. This was not confounded by demographic factors (age, smoking status, race, obesity), thus supporting the robustness of the approach. We demonstrate, for the first time, that nano-architectural alterations occur in prostate cancer field carcinogenesis and can be exploited to predict prognosis of early stage PCa. This approach has promise in addressing the clinically vexing dilemma of management of Gleason 6 PCa and may provide a paradigm for dealing with the larger issue of cancer overdiagnosis.